Treatment satisfaction of patients with psoriasis - Schaarschmidt, Marthe-Lisa; Kromer, Christian; Herr, Raphael M.; Schmieder, Astrid; Goerdt, Sergij; Peitsch, Wiebke K. (Acta Dermato-Venereologica, 2015)
Treatment satisfaction of patients with psoriasis largely depends on the treatment modality, but evidence on preferences for specific medications is scarce. Here we assessed treatment satisfaction of 200 participants with moderate-to-severe psoriasis from a German University hospital with a 5-point scale and the Treatment Satisfaction Questionnaire for Medication (TSQM) and determined sociodemographic and disease-related influence factors. Participants obtaining biologicals and traditional systemic medications were significantly more satisfied than those receiving phototherapy or topical agents (TSQM = 323.3, 288.0, 260.6 or 266.8; p < 0.001). The highest TSQM score was calculated for ustekinumab (350.1), followed by acitretin (338.1), adalimumab (323.0), fumaric acid esters (304.7), infliximab (300.2), etanercept (298.8), and methotrexate (272.3; p < 0.001). High disease-related quality of life impairment (β = –0.437, p < 0.001) and psoriatic arthritis (β = –0.185, p = 0.005) were associated with decreased satisfaction. Optimising satisfaction is essential to improve adherence and outcome. We show high preferences for biologicals, particularly ustekinumab, but also good satisfaction with certain traditional medications.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Biologicals; Preferences; Psoriasis; Systemic therapy; Treatment satisfaction; Ustekinumab